2013
DOI: 10.1007/s12264-013-1300-8
|View full text |Cite
|
Sign up to set email alerts
|

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study

Abstract: People with schizophrenia exhibit impaired social cognitive functions, particularly emotion regulation. Abnormal activations of the ventral medial prefrontal cortex (vMPFC) during emotional tasks have been demonstrated in schizophrenia, suggesting its important role in emotion processing in patients. We used the resting-state functional connectivity approach, setting a functionally relevant region, the vMPFC, as a seed region to examine the intrinsic functional interactions and communication between the vMPFC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 106 publications
1
22
0
1
Order By: Relevance
“…49,50 Additional studies identify amygdala as a source of local circuit impairment in schizophrenia. 18,[51][52][53] Importantly, the current study did not identify a distributed global impairment of amygdala functional connectivity in schizophrenia across widespread cortical regions, as one may have predicted if amygdalar function with distributed cortical systems was grossly abnormal. Therefore, the current data suggest that the primary abnormality in symptomatic patients may occur in amygdala-OFC connectivity, in line with meta-analyses suggesting possible subtle alterations in amygdala activation in schizophrenia.…”
Section: Amygdala-orbitofrontal Connectivity Is Altered In Chronic Anmentioning
confidence: 58%
“…49,50 Additional studies identify amygdala as a source of local circuit impairment in schizophrenia. 18,[51][52][53] Importantly, the current study did not identify a distributed global impairment of amygdala functional connectivity in schizophrenia across widespread cortical regions, as one may have predicted if amygdalar function with distributed cortical systems was grossly abnormal. Therefore, the current data suggest that the primary abnormality in symptomatic patients may occur in amygdala-OFC connectivity, in line with meta-analyses suggesting possible subtle alterations in amygdala activation in schizophrenia.…”
Section: Amygdala-orbitofrontal Connectivity Is Altered In Chronic Anmentioning
confidence: 58%
“…For example, contrary to hyperconnectivity, a study using an ROI in the ventral MPFC showed decreased resting-state FC between the ventral MPFC and the default mode network regions (such as the anterior MPFC, right middle temporal lobe, hippocampus, parahippocampus, and amygdala) in chronic schizophrenic patients. And the decreased FC between the ventral MPFC and right medial-temporal regions has been correlated with the poorer regulation of emotion [75] .…”
Section: Medial Pfc and The Default Mode Networkmentioning
confidence: 98%
“…Schizophrenia patients show hyperactivation of the amygdala and underconnectivity of the VMPFC-amygdala pathway (Fan et al, 2013;Pankow et al, 2013). Therefore, it is probable that in schizophrenia, like ASD, increased activity in the amygdala caused by hippocampal hyperactivation induces desensitization and dysregulation of the VMPFC.…”
Section: Social Cognitive Deficits In Schizophreniamentioning
confidence: 99%